NOURISHING THE MIND: INTEGRATING FREE NUTRITIONAL MEAL POLICY WITH PSYCHOLOGICAL DEVELOPMENT AND GREEN HUMAN RESOURCES IN ELEMENTARY SCHOOLS - Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin; Hastuti Handayani Harahap (CV. Radja Publika, 2025)
The Free Nutritious Meal Program (MBG) is a strategic government policy aimed at improving the nutritional quality of elementary school children while strengthening human resource development from an early age. This study aims to analyze the nutritional status and consumption patterns of elementary school students, examine the influence of MBG on students' psychological development, particularly their concentration on learning, motivation, and school attendance, and evaluate the program's role in shaping healthy eating behaviors and sustainable lifestyle habits from a green human resource perspective. The research approach uses a descriptive qualitative method with literature and policy analysis, supported by empirical findings from previous studies and reports from international institutions. The results show that the Free Nutritious Meal Program contributes positively to improving students' nutritional status and shifting consumption patterns towards healthier ones. In addition, MBG has been shown to support increased concentration on learning, motivation, and school attendance. However, the integration of green human resource values ​​in the implementation of MBG is still not optimal and tends to be partial. Therefore, a holistic and sustainable MBG policy integration model is needed that involves schools, families, and communities. This study concludes that MBG functions not only as a nutritional fulfillment program but also as a strategic instrument for developing green human resources that are healthy, have character, and are sustainable from an early age.